An Assessment of ICT Literacy Among Secondary School Students in a Rural Area of Kwara State, Nigeria: A Community Advocacy Approach - M.A., Mabayoje; A., Isah; A. O., Bajeh; R. A., Oyekunle (Covenant Journal of Informatics and Communication Technology, 2016)
In recent times, public schools in Nigeria have enjoyed some benefits in terms of deployment of Information and Communication Technologies (ICTs), but no constant attention and continuous interest is paid to fill the digital gap between schools in the rural and urban areas. The contribution of private sectors in the education system has elevated the use of ICT in both private and public schools especially in the urban areas of Nigeria. However, schools in rural areas have not benefitted much in this area. This research used community advocacy program referred to as COBES (Community Based Experience Scheme) to assess ICT literacy of secondary school students in a rural area of Kwara State, Nigeria. The study employed mixed research approach that combined both quantitative and qualitative data collection strategies. The initial findings of the study revealed low level of ICT skills among secondary school students in the rural area. Although, majority of the students who served as the respondents claimed they have computer teacher and can operate computer systems, yet, the study showed that there is dearth of ICT facilities for hands-on training. Nevertheless, through the one week long COBES program, the findings from three focus group discussion conducted at the end of the COBES program showed that studentsâ€Ÿ interest to use ICT increased and majority of them expressed their willingness to continue interacting with computer and internet facilities. Findings further revealed that the main reason for low ICT skills is the lack of ICT facilities for teaching and learning. The study recommended that ICT project implementationÂ should be uniform in all public schools in Nigeria, irrespective of whether it is located in the urban or rural area, adequate and skilled computer studies teachers should be made available and government should put in place mechanisms that will ensure proper maintenance of the ICT facilities